Safety and efficacy of remimazolam besylate in patients undergoing colonoscopy: A multicentre, single-blind, randomized, controlled, phase Ⅲ trial - Wang, Ximei; Hu, Xiaolei; Bai, Nianyue; Li, Lie; Zhang, Min; Cheng, Zhigang; Guo, Qulian (Frontiers in Pharmacology, 2022)
Study objective: The objective of the study was to evaluate the safety and efficacy of remimazolam besylate versus propofol injection in patients undergoing colonoscopy. Design: A multicenter, randomized, non-inferiority, single-blind, parallel-controlled clinical trial. Setting: Operating room. Patients: Patients aged 18 65 years (American Society of Anesthesiologists [ASA] classification I-III) undergoing a diagnostic or therapeutic colonoscopy. Interventions: Patients were administered intravenous injection of remimazolam besylate or propofol (active comparator) for sedation. Measurements: Modified Observer’s Assessment of Alertness/Sedation [MOAA/S] scores of the included patients were assessed before dosing, 1 min, 1.5 min, 2 min, 2.5 min, and 3 min after the start of dosing, and then every 1 min until the MOAA/S score reached 5 on three consecutive occasions. Main Results: A total of 360 patients received remimazolam and 120 patients received propofol. The incidence of adverse events (67.8% vs. 84.2%, p<0.001) was significantly lower in patients administered remimazolam compared to propofol. There was no significant difference in sedation success rates (full analysis set [FAS]: 98.9% vs. 99.2%; remimazolam vs. propofol). Remimazolam had a significantly longer onset of action, but the difference was not considered clinically significant (1.45 min vs. 1.24 min, remimazolam vs. propofol). Propofol achieved a deeper level of sedation (mean MOAA/S score 0.5 vs. 0.2; remimazolam vs. propofol). Mean time to discharge after the end of the last administration of study drug (20.3 vs. 21.8 min, p=0.020) and incidence of injection pain was significantly lower in patients administered remimazolam (2.3% vs. 35.3%, p<0.001). Incidence of oxygen desaturation was significantly higher in patients administered propofol compared to patients administered remimazolam (6.7% vs. 1.1%, p<0.003). Similarly, incidence of hypotension was more frequent in patients administered propofol compared to patients administered remimazolam (29.2% vs. 10.6%, p<0.001). Conclusions: Remimazolam besylate had a better safety and tolerability profile and similar sedative efficacy to propofol in patients undergoing a diagnostic or therapeutic colonoscopy in China, suggesting that remimazolam besylate has potential as a sedative agent for colonoscopy.